Crash landing in Cape Town : testing the port-of-entry conceptualisation and examining Cape Town's spatial policy for cognisance of migrant's diverse spatial and livelihood strategies - East, Christopher Mark (School of Architecture, Planning and Geomatics, 2014)
Since the fall of Apartheid, and the subsequent dawn of democracy, South Africa has increasingly become a destination space for asylum seekers and refugees from throughout Africa. It is apparent that many of these asylum seekers and refugees (collectively defined as migrants within this dissertation) although granted comprehensive rights by the South African Constitution, are unable to access or 'realise' these rights. Migrants throughout the country have been encouraged to integrate into South African society and become active agents of their own integration. This has resulted in the Department of Home Affairs granting all individuals in possession of an asylum seeker permit the right to work, negating the need for work permits within migrant communities. This has resulted in most migrant communities living within the urban fabrics of South Africa's cities. As Cape Town has become a primary destination space for migrants, its spatial policy requires cognisance of their diverse spatial and livelihood strategies in order to augment, rather than undermine, their mechanisms of integration. Port-of-entry neighbourhoods, as documented in cities such as New York and Johannesburg, are neighbourhoods in which such mechanisms manifest, deeming them strategic areas for newcomers to the city. The aims of this dissertation are firstly to construct a fine-grained case study of migrants' spatial and livelihood patterns within Cape Town, and in so doing test the port-of-entry conceptualisation within the Cape Town context. Increasingly apparent in Cape Town's case study is the emerging spatial pattern of migrant rich neighbourhoods. This pattern is emerging in a bilinear fashion in the old, often degrading, middle class neighbourhoods that straddle the northern and southern rail lines. Secondly, this dissertation aims to test and analyse Cape Town's spatial policy for its cognisance towards these spatial and livelihood strategies. Evident within Cape Town's spatial policy is the pursuit of spatial justice and rectification of the city's spatial marginalisation, yet there is no cognisance of the diverse migrant strategies within the city. Lastly, this paper suggests an alternative planning approach for Cape Town's migrant rich neighbourhoods, particularly Maitland, Parow and Bellville, which strongly exhibit the characteristics normally found in port-of-entry neighbourhoods. A number of non-spatial migrant policy suggestions are also promulgated in order to rectify the on-going marginalisation of migrants within South African society.